Finite element method in estimation of lag time of rainfall recharge to Holocene groundwater aquifer in Hung Yen province - Hoang, Nguyen Van; Roi, Nguyen Duc (Vietnam Journal of Earth Sciences, 2015)
In the Red River delta, Holocene aquifer has main recharge from rainfall and irrigation. The recharge is much dependent upon the unsaturation-saturation condition of the semipermeable layer covering the aquifer. The paper presents the analysis of moisture transfer in this covering semipermeable layer to estimate the lag time of rainfall recharge to the Holocene aquifer in Hung Yen province in the Red River delta. A finite element modeling had been developed and applied for this purpose. The lag time results have been based on the condition that the degree of saturation of 90% or more is representative for saturation water movement, and therefore the rainfall is actually recharging the aquifer via saturated flow through the covering semipermeable layer. The lag time is 3 days for continuous wet condition from the rainfall if the thickness of the semipermeable layer is 2m, and 5.5 days if the thickness is 3m. For consecutive wet day and dry day condition the lag time is 4 days if the thickness is 2m and 13 days if the thickness is 3m. Therefore, the duration of rainfall for recharge estimation for the study area would be up to about two weeks.References Vu The Hai, 2005: Study on low flow rate and low pressure sprinkler watering for plants in Vietnam northern mountainous and hilly areas. Doctoral diserstesia thesis-Hanoi Water Resources University (in  Vietnamese). Huyakorn Pinder, 1987: Computational method in subsurface flow. Academic Press. Nguyen Van Hoang, 2012-2015: Research study No. NCCB-ĐHUD.2012-G/04 "Compilation of FEM software for groundwater movement and solute-transport in groundwater - application to the central coastal area". Jacob Bear and Arnold Verruijt, 1987: Modeling groundwater flow and pollution, D. Reidel Publishing Company, Dordrecht, Holland. Jiunsheng Li and Hiroshi Kawano, 1997: Sprinkler Water Utilization Efficiency. Journal of International Rainwater Catchment Systems, Vol, 3, No, 1, July, 1997, pp. 41-51. Polubarinova-Kochina, 1977: Theory of Groundwater Movement. Higher education publishing house. Moscow (in Russian). Omer Nawaf Maaitah, 2012: Soil-Water Characteristic Curve Model-Silty Sand Soil. Jordan Journal of Civil Engineering, Volume 6, No. 1, 2012 Zienkiewics O.C. and Morgan K., 1983: Finite Elements and Approximation. John Willey & Sons. Department of geology and mineral resources-MoNRE. 2013. Groundwater monitoring in Bac Boc Plain. Center for Geological Information and Archive-MoNRE. Hung Yen Statistic Office, 2014: Hung Yen statistical book year 2013. National Center for Meteorology and Hydrology-MoNRE, 2013: Meteorological and Hydrological monitoring data.